Corrosion and corrosion control : an introduction to corrosion science and engineering - Revie, R. Winston 1944-; Uhlig, Herbert Henry, 1907- (Wiley-Interscience, a John Wiley & Sons, Inc., Publication, 2008)
This is an updated edition of the introductory text on corrosion science and engineering by Revie (CANMET Materials Technology Laboratory, Canada) and the late Uhlig (former director of Massachusetts Institute of Technology's Corrosion Laboratory). The main emphasis is on quantitative presentation, explanation, and analysis. The basics are presented in the first five chapters, which cover the definition and importance of corrosion, electrochemical mechanisms, thermodynamics of corrosion tendency and electrode potentials, thermodynamics and Pourbaix diagrams, and the kinetics of polarization and corrosion rates. The remaining chapters address passivity, iron and steel, effect of stress, atmospheric corrosion, corrosion in soils, oxidation, stray-current corrosion, cathodic protection, metallic coatings, inorganic coatings, organic coatings, inhibitors and passivators, treatment of water and steam systems, alloying stainless steels for corrosion resistance, copper and copper alloys, aluminum and aluminum alloys, magnesium and magnesium alloys, nickel and nickel alloys, cobalt and cobalt alloys, titanium, zirconium, tantalum, and lead.